EU-ASEAN free trade agreement(s) – prospects and challenges for inter-regional FTA - Mazur, Grzegorz (Umowy o wolnym handlu UE-ASEAN - perspektywy i wyzwania dla międzyregionalnych SWH, 2017)
In 2007 the EU and ASEAN launched negotiations on a free trade agreement between the regions. However, 2 years later, the inter-regional negotiations were paused due to the slow progress . As an alternative the EC started individual negotiations with those countries that wished to sign a bilateral FTA. Firstly, it initiated talks with Singapore in 2010 which was then followed by Malaysia, Vietnam, Thailand, the Philippines and Indonesia. By the half of 2017 the EU concluded the FTAs with Singapore and Vietnam which are yet to be ratified. Four other countries negotiate the agreements with many challenges and issues to be addressed in bilateral talks. Although official declarations say about replacing those individual agreements by one EU-ASEAN FTA in future, it will be difficult to achieve due to differences in economic interest among ASEAN members, differential progress within the ongoing negotiations and even the reluctance of some countries to join the FTA with the EU
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 486, s. 141-154
Keywords: EU; ASEAN; FTA; free trade agreement; EUSFTA; UE; SWH; strefa wolnego handlu